1997
DOI: 10.1097/00005768-199701000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Greater cross education following training with muscle lengthening than shortening

Abstract: The hypothesis was tested that the magnitude of cross education is greater following training with muscle lengthening than shortening. Changes in contralateral concentric, eccentric, and isometric strength and vastus lateralis and biceps femoris surface electromyographic (EMG) activity were analyzed in groups of young men who exercised the ipsilateral quadriceps with either eccentric (N = 7) or concentric (N = 8) contractions for 36 sessions over 12 wk. Control subjects (N = 6) did not train. Concentric traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
204
1
7

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(232 citation statements)
references
References 23 publications
20
204
1
7
Order By: Relevance
“…The submaximal and isometric contribution resulted in a 19% increase in the maximal voluntary strength of the wrist flexors of the trained limb. The increase in strength of the trained synergist muscle is consistent with previous research, which confirms that isometric strength training increases strength of the trained limb (Hortobágyi et al 1997;Zhou et al 2000;, even at training intensities of 10-20% of MVC (Laidlaw et al 1999;Kobayashi et al 2014). Such an increase in strength of the trained synergist, likely accounts for the increase in strength of the untrained synergist wrist flexors, which supports the strong correlation shown in this study.…”
Section: Unilateral Strength Training Improves Strength Of the Untraisupporting
confidence: 92%
“…The submaximal and isometric contribution resulted in a 19% increase in the maximal voluntary strength of the wrist flexors of the trained limb. The increase in strength of the trained synergist muscle is consistent with previous research, which confirms that isometric strength training increases strength of the trained limb (Hortobágyi et al 1997;Zhou et al 2000;, even at training intensities of 10-20% of MVC (Laidlaw et al 1999;Kobayashi et al 2014). Such an increase in strength of the trained synergist, likely accounts for the increase in strength of the untrained synergist wrist flexors, which supports the strong correlation shown in this study.…”
Section: Unilateral Strength Training Improves Strength Of the Untraisupporting
confidence: 92%
“…Observations of increased surface EMG [79,80,81,82,83,84] , increased motor unit firing rates [85,86] , cross education [82,87,88,89,90,91] and enhanced reflex potentiation [92,93,94] are consistent with the possibility but none provides conclusive evidence.…”
Section: 3 the Influence Of Resistance Trainingmentioning
confidence: 99%
“…During prostration, the elbows are flexed which causes a moderate lengthening effect on the muscles of the upper arm. It has been reported that lengthening exercises provide more benefits to the human musculoskeletal system than shortening exercises 21,22) . By using prostration in Salat as the case for investigation, we have proven that Salat produces an effect similar to the effect of a standard stretching exercise, the child's pose.…”
Section: Discussionmentioning
confidence: 99%